Effects of Various Phytase Concentrations in Diets with Low-phytate Corn on Broiler Chick Performance and Nutrient Use - Baker, N.J.; Parsons, A.S.; Moritz, J.S. (International Journal of Poultry Science, 2007)
Research indicates a reduction in phosphorus content of broiler excreta with the supplementation of phytase to corn-soybean meal based diets or with the use of Low Phytate Corn (LPC). This study examined how broiler chicks are impacted by phytase supplementation to a LPC [0.136% Phytate Phosphorus (PP) by analysis] based diet. Different dietary inclusion levels from a 2,500 or a 5,000 FYT/g of Peniophora lycii phytase product were used as experimental treatments. Following a six day pretest, 576 broiler chicks were randomly assigned to one of 12 dietary treatments, using eight diet replicates and six birds per cage. Live performance, tibia ash, mineral digestibility and apparent metabolizable energy were determined. The percent of phosphorus that may have been spared due to each phytase treatment was calculated using response curves created with increasing levels of monocalcium phosphate. Results demonstrated that phytase supplementation to a LPC based diet had a positive impact on broiler chick growth. However, this impact is expressed to a lesser extent than would be expected for normal corn. In addition, phytase efficacy did not vary based on the concentration of phytase product, likely due to adequate mix uniformity.